Lifespan Development. - Anthis, Kristine (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

EdPsych Modules. - Durwin, Cheryl C. (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

Forgiving One Page at a Time: The Diary of Your Journey to Restoration and Confidence - Affinito, Mona Gustafson (AuthorHouse, 2007)
Keywords: Forgiveness; dept.psy; faculty_collection

Rats’ choices between one and two delayed reinforcers - Mazur, James E (Learning & Behavior, 2007)
Rats chose between alternatives that differed in the number of reinforcers and in the delay to each reinforcer. A left leverpress led to two reinforcers, each delivered after a fixed delay. A right leverpress led to one reinforcer after an adjusting delay. The adjusting delay was increased or decreased many times in a session, depending on the rat's choices, in order to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Both the number of reinforcers and their individual delays affected the indifference points. The overall pattern of results was well described by the hyperbolic-decay model, which states that each additional reinforcer delivered by an alternative increases preference for that alternative but that a reinforcer's effect is inversely related to its delay. Two other possible delay-discounting equations, an exponential equation and a reciprocal equation, did not produce satisfactory predictions for these data. Adding an additional free parameter to the hyperbolic equation as an exponent for delay did not appreciably improve the predictions, suggesting that raising delay to some power other than 1.0 was unnecessary. The results were qualitatively similar to those from a previous experiment with pigeons (Mazur, 1986), but quantitative differences suggested that the rates of delay discounting were several times slower for rats than for pigeons.
Keywords: *Choice Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; *Time Perception; Animals; Male; Models, Theoretical; Rats; Rats, Sprague-Dawley; animal behavior; animal experiment; article; conditioning; dept.psy; hyperbolic decay model; mathematical model; nonhuman; pigeon; predictive validity; rat; reinforcement

Species differences between rats and pigeons in choices with probabilistic and delayed reinforcers - Mazur, James E. (Behavioural Processes, 2007)
An adjusting-delay procedure was used to study rats' choices with probabilistic and delayed reinforcers, and to compare them with previous results from pigeons. A left lever press led to a 5-s delay signaled by a light and a tone, followed by a food pellet on 50% of the trials. A right lever press led to an adjusting delay signaled by a light followed by a food pellet on 100% of the trials. In some conditions, the light and tone for the probabilistic reinforcer were present only on trials that delivered food. In other conditions, the light and tone were present on all trials that the left lever was chosen. Similar studies with pigeons [Mazur, J.E., 1989. Theories of probabilistic reinforcement. J. Exp. Anal. Behav. 51, 87-99; Mazur, J.E., 1991. Conditioned reinforcement and choice with delayed and uncertain primary reinforcers. J. Exp. Anal. Behav. 63, 139-150] found that choice of the probabilistic reinforcer increased dramatically when the delay-interval stimuli were omitted on no-food trials, but this study found no such effect with the rats. In other conditions, the probability of food was varied, and comparisons to previous studies with pigeons indicated that rats showed greater sensitivity to decreasing reinforcer probabilities. The results support the hypothesis that rats' choices in these situations depend on the total time between a choice response and a reinforcer, whereas pigeons' choices are strongly influenced by the presence of delay-interval stimuli. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: *Association Learning/ph [Physiology]; *Choice Behavior/ph [Physiology]; *Probability Learning; *Reinforcement, Psychology; *Time Perception/ph [Physiology]; Animals; Columba; Columbidae; Delay-interval stimuli; Delayed reinforcers; Probabilistic reinforcers; Rats; Rats, Sprague-Dawley; Rattus; Species Specificity; Time Factors; animal experiment; article; behavioral response; controlled study; decision making; dept.psy; food; food intake; gamebird; nonhuman; probability; rat; reinforcement; rodent; species difference; stimulus

Choice in a successive-encounters procedure and hyperbolic decay of reinforcement. - Mazur, James E (Journal of the experimental analysis of behavior, 2007)
Pigeons responded in a successive-encounters procedure that consisted of a search state, a choice state, and a handling state. The search state was either a fixed-interval or mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search state, the choice state was presented, in which the center key was off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search state (by pecking the left key). During the choice state, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). In some conditions, both the short and long alternatives were fixed-time schedules, and in other conditions both were mixed-time schedules. Contrary to the predictions of both optimal foraging theory and delay-reduction theory, the percentage of trials on which pigeons accepted the long alternative depended on whether the search and handling schedules were fixed or mixed. They were more likely to accept the long alternative when the search states were fixed-interval rather than mixed-interval schedules, and more likely to reject the long alternative when the handling states were fixed-time rather than mixed-time schedules. This pattern of results was in qualitative agreement with the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Choice; Choice Behavior; Columbidae; Delay-reduction theory; Hyperbolic-decay model; Key peck; Male; Optimal foraging theory; Pigeons; Reinforcement (Psychology); Successive-encounters procedure; animal; article; decision making; dept.psy; male; peer-reviewed; pigeons and doves; reinforcement